Diversity in Determining Maturity Age in Indonesian Law: Maqashid al-Sharia Perspective - Ali Sodiqin; Al-Robin Al-Robin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
This article explores the emergence of diversity in determining the age of maturity in Indonesian laws, particularly in civil, penal, marriage, and citizenship laws. Maturity is a crucial element in determining a legal act. Therefore, the diversity of its determination can lead to overlap and ambiguity in determining the validity of legal action and legal accountability. This raises the question of why there is a difference in the determination of maturity age and its factors. This diversity problem is analyzed in maturity age using the maqashid al-sharia approach, using Jasser Auda’s system theory. The study shows that differences in legal proficiency required cause differences in the determination of maturity age in legislation, a legal paradigm used as a basis, and differences in the law's scope. From the maqashid al-sharia perspective, maturity age occupies a position as a wasilah or a strategy to achieve legal purposes, thus allowing for diversity. The more interests are protected, the higher of age is set. The diversity of maturity ages has an interrelated hierarchy without causing any contradictions between laws. The maturity age difference is intended to fulfill legal authority requirements, proficiency to act, and authority to act, with their specifics.